Pengaruh Kualitas Produk, Harga dan Kualitas Pelayanan Terhadap Kepuasan Pengguna Produk Merek Onna di PT. Tunas Interior - Salmon Situmoran; Riandani Rezki Prana; Dewi Shinta Wulandari Lubis (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2020)
This study aims to determine the effect of product quality, price and quality of service to the satisfaction of users of the Onna brand products at PT. Tunas Interior Batam. The samples in this study were 89 consumers who bought Onna products at PT. Tunas Interior in January 2018 until December 2018, sampling using the Slovin formula with a population of 851 people. Data analysis using Multiple Regression test, hypothesis testing using the coefficient of determination (R2), partial test (t test), and simultaneous test (F test), while processing using SPSS 20. The results of research using the coefficient of determination test showed that the quality of the product, price and quality of service are able to explain its existence to the variable of customer satisfaction, besides that partially product quality, price and service quality has a positive and significant effect on customer satisfaction, simultaneously product quality, price and quality of service have a positive and significant effect on customer satisfaction.